2017
DOI: 10.1007/s40265-017-0691-7
|View full text |Cite
|
Sign up to set email alerts
|

Drug Therapy for Stable Angina Pectoris

Abstract: Chronic stable angina pectoris refers to the predictable, reproducible occurrence of pressure or a choking sensation in the chest or adjacent areas caused by myocardial ischemia in association with physical or emotional stress, and cessation of exertion and or sublingual nitroglycerin invariably relieves the discomfort. It is a common presenting symptom of severe narrowing of one or more coronary arteries, non-obstructive coronary arteries, or even when the coronary arteries are angiographically normal. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 144 publications
0
22
0
4
Order By: Relevance
“… 33 It has been suggested that organic nitrite bioactivation occurs via glutathione transferases. 36 38 GTN is a recommended symptomatic therapy for angina pectoris, 17 but tolerance development may be an obstacle to long-term infusions of GTN. In clinical use, it is advantageous to use an NO donor like an organic nitrite lacking tolerance development that also fulfills the summary beneficial effects of GTN in the respective disease condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 It has been suggested that organic nitrite bioactivation occurs via glutathione transferases. 36 38 GTN is a recommended symptomatic therapy for angina pectoris, 17 but tolerance development may be an obstacle to long-term infusions of GTN. In clinical use, it is advantageous to use an NO donor like an organic nitrite lacking tolerance development that also fulfills the summary beneficial effects of GTN in the respective disease condition.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Despite tolerance development, organic nitrates – particularly GTN – are effective and recommended antianginal medications. 17 Certain NO donors, notably organic nitrites, seem to provoke less development of tolerance possibly due to a better maintained NO generation during infusions in vivo. 18 – 20 Recently, we synthesized novel NO donors for IV infusion, the organic mononitrites of 1,2-propanediol (PDNO, Figure 1 ), which were potent vasodilators, especially in the pulmonary circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that the prognosis is better than that reported in published data [34]. However, individual prognoses can vary considerably, depending on baseline clinical, functional, and anatomic characteristics.…”
Section: History Of Angina Pectorismentioning
confidence: 96%
“…Выбор конкретного базисного препарата (первой линии) или его комбинаций с другими препаратами (вто-рой линии) следует проводить согласно общепринятым рекомендациям: с учетом индивидуального подхода, тяжести стенокардии, гемодинамических показателей: частоты сердечных сокращений (ЧСС) и артериального давления (АД), наличия коморбидных состояний [1][2][3]. Дополнительно пациентам следует назначать статины и ацетилсалициловую кислоту.…”
Section: Introductionunclassified